Global optimisation of functional requirements and tolerance allocations based on designer preference modelling. Issue 9 (1st September 2016) - Ledoux, Yann; Teissandier, Denis; Sebastian, Patrick
ABSTRACT: The allocation of design and manufacturing tolerances has a significant effect on the final performance of products and the associated manufacturing costs. Although this phase is crucial in the early stages of product design, there is a lack of tools to provide support for designers. The main originality of this study is to propose an integrated optimisation scheme based on a particular ontological model, which structures the design problem from the functional requirements stage to the definition of quantified objectives for optimisation. Design priorities are integrated by weighting every design objective. The mechanism studied here is a helicopter turboshaft engine. The aim is to determine optimal tolerance values according to several scenarios. A comparison between classical distribution of tolerance values (iso-distribution) and a tolerance distribution subject to manufacturing costs is proposed. Finally, ontological modelling is used to optimise the position of the mechanical joints of the mechanism, the tolerance values and the associated costs. This last result demonstrates the advantage of integrating both the tolerance optimisation related to manufacturing cost and the joint positions of the mechanism in the early phase of the design.